VATAGAJENDRASINGH RASA - IN THE MANAGEMENT OF AMAVATA: A REVIEW (AYUSHDHARA, 2017)
The disease Amavata which can be correlated Rheumatoid arthritis (RA) in modern medicine, now a days it is a common problem due to changed lifestyle, food habits and lack of physical activities. It is the common most crippling and disabling disorder in the world. Ama (indigested end product of food) and Vata (one of the three Dosha) both are equally important for the establishment of the disease, predominantly produces Sandhishoola (joint pain), Sandhishotha (joint swelling), Gaurava (heaviness), Jwara (fever). The prevalence of RA is approximately 0.8% of the population (range 0.3 to 2.1%); women are most commonly affected. There are several formulations for the management of Amavata, but only that, which can bring about a cure, is a correct medicine. Use of herbomineral formulations is common in present Ayurvedic practice. Ayurvedic drug ‘Vatagajendrasingh Rasa’ is a unique formulation mentioned in Bhaishajyaratnawali for the management of Amavata. The aim of the study is to evaluate the possible mode of action of the formulation in the management of Amavata. The main ingredients are Kajjali, Abhraka Bhasma, Tamra Bhasma, Loha Bhasma, Naga Bhasma, Shuddha Vatsanabha, Shuddha Tankana, Shuddha Hinga, Shuddha Jatiphala etc. Purpose of composition is Sampraptibhanga (break the pathogenesis) by Agnideepana (increase appetite), Amapachana (digestion) and management of symptoms and complications (Ashthivikruti, Sandhikunjana, Sankocha, Khanjatva, Agnidaurablya etc.) In Ativriddha (Chronic) Amavata.